On the Filtration Efficiency of Composite Media Composed of Multiple Layers of Electret Media - Peng Wang; Da-Ren Chen (Aerosol and Air Quality Research)
Abstract This study aimed to explain the discrepancy reported in previous studies between the observed and the calculated filtration efficiencies of a composite formed of multiple electret medium layers. After measuring the composite’s filtration efficiency using particles divided by size and electrical charge status, viz., those possessing no charge, a single charge, and a stationary charge according to the Boltzmann distribution, we traced the discrepancy to the latter attribute. Hence, to accurately predict the filtration efficiency of multi-layered electret media, we must account for the test particles’ electrical charge distribution.